Perlindungan Korban Tindak Penganiaayaan Dalam Hukum Pidana Indonesia Dan Hukum Pidana Islam (Perspektif Restorative Justice) - Fawaid, Bahrul (Universitas Merdeka Madiun, 2018)
Process of resolving acts of persecution in Indonesian criminal law still have a number of things to fixed. One of them is the problem of dissatisfaction among the parties because they feel they have not received justice and benefit from court decisions, which is the end of the legal settlement process. Indonesian criminal law has not given much attention to the protection of victims of acts of persecution. What the victims need for recovery, the resolution of what the victims want, and the active participation of victims in resolving acts of persecution have not yet been realized optimally. Victims of persecution seem to only be complementary in the whole law process. Therefore, this paper seeks to examine how the protection the victims of persecution in Indonesian criminal law and Islamic criminal law from the perspective of restorative justice.